Cross-cultural and psychometric validation of the Fraboni scale of ageism in Peruvian nursing students - Jack Roberto Silva Fhon; Catalina Olimpia Bello-Vidal; Maritza Evangelina Villanueva-Benites; Orfelina Arpasi-Quispe; Zoila Esperanza Leitón-Espinoza; Walter Capa-Luque (Tehran University of Medical Sciences, 2024)
Background & Aim: The elderly population has increased in the last decades and they are often discriminated against in society due to their age. This study aimed to perform the cross-cultural and psychometric validation of the Fraboni Scale of Ageism in Peruvian nursing students. Methods & Materials: This is a cross-sectional methodological study, carried out in four universities in Peru in which 959 nursing students participated. For the adaptation process, the forward-backward method of the original English version into Spanish was used. For the content analysis, the study was carried out with the participation of specialist judges, while confirmatory factor analysis was used for the internal structure of the construct as invariance of measurement. Reliability was estimated by internal consistency for categorical items. Results: The total content validity estimated with CVI was 0.97. The internal structure of the construct was found to be appropriate for the respecified 20-item model (CFI and TLI=0.94, RMSEA=0.07, and SRMR=0.05). The 20-item bi-factor model presented excellent fit indices (CFI=0.96 and TLI=0.95, RMSEA=0.06 and SRMR=0.04), being the best model for construct validity. Measurement invariance by sex was confirmed for all four models (configural, metric, strong, and strict). The three-dimensional model (ω=0.93) as well as the bi-factor model (ωH=0.88) showed high reliability for the scale scores. Conclusion: This study demonstrates that the 20-item Peruvian version of the Fraboni Scale of Ageism shows validity and reliability for its scores. In addition, the scale score is invariant by sex.